Contemporary research in accounting, auditing and finance - Kurnaz, Ersin; Serçemeli, Murat (Cambridge Scholars Publishing, 2019)
The business world needs to follow developments in the areas of accounting, auditing and finance in order to be able to adapt to globalization, technological advances and changing human needs. This book explores current issues in accounting, auditing and finance from a scientific point of view, and makes various suggestions for their solutions. In this context, the contributions here take into account the latest developments in the field and utilise a wide range of resources. The reader will learn about participation banks, audit risk, financial manipulation, forensic accounting, accounting er.